Efektivitas Cognitive Behavioral Therapy pada Remaja dengan Adiksi Internet - Samosir, Melissa Novitasari; Keliat, Budi Anna; Hargiana, Giur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This systematic review aims to examine the effectiveness of thought and behavior therapy or cognitive behavioral therapy in recovering from internet addiction in adolescents. The method used in the systematic review was carried out on the Science Direct, Proquest, Scopus, Sage Journal and Springer Link databases with searches carried out between September-November 2023. Articles were filtered according to inclusion criteria and had been critically assessed using criteria from the Joanna Briggs Institute (JBI). The research results in the initial search obtained 3,793 articles, and after filtering using inclusion criteria, 10 articles were obtained that were in accordance with the aim of the article review. The search results show that thought and behavior therapy or cognitive behavioral therapy has proven to be effective in recovering from internet addiction in teenagers. The conclusion is that a well-designed cognitive behavioral therapy program by providing support to adolescents and instilling positive behavior can help clients from the threat of internet addiction again. Keywords: Addiction, Adolescent, Cognitive Behavioral Therapy, Internet.